Culturally Responsive Physics Education: A Bibliometric Mapping of Ethnoscience and Local Wisdom Integration (2010–2025) - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2026)
The integration of local culture and indigenous knowledge into physics education has gained substantial scholarly attention over the past decade, reflecting a broader global movement toward culturally responsive pedagogy. This study presents a comprehensive bibliometric analysis of research on ethnoscience and local wisdom integration in physics education, drawing on Scopus-indexed publications from 2010 to 2025. Using VOSviewer and Biblioshiny-Bibliometrix software for network visualization and scientific mapping, the analysis examines publication trends, geographic and institutional contributions, key authors, thematic clusters, and emerging research directions. The findings reveal a gradual but accelerating annual growth in publications, with Indonesia emerging as the dominant contributor, reflecting the country's rich cultural diversity and active physics education research community. The Journal of Physics: Conference Series and AIP Conference Proceedings are identified as the primary publication outlets. Four major thematic clusters emerge: culture-physics integration, influencing factors in culturally based learning, methodological approaches, and supporting elements including digital innovation. Central themes connecting these clusters include ethnoscience, Islamic physics, digital learning tools, and contextual pedagogy. The analysis also identifies significant research gaps, including limited geographic diversity beyond Indonesia, narrow focus on motion and heat topics, and insufficient development of validated instructional materials. This study contributes to the growing body of knowledge on culturally responsive science education by providing a systematic mapping of the research landscape and offering evidence-based recommendations for future inquiry.